2014
DOI: 10.1016/j.anihpc.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior for critical Patlak–Keller–Segel model and a repulsive–attractive aggregation equation

Abstract: In this paper we study the long time asymptotic behavior for a class of diffusion-aggregation equations. Most results except the ones in Section 3.3 concern radial solutions. The main tools used in the paper are maximum principle type arguments on mass concentration of solutions, as well as energy method. For the Patlak-Keller-Segel problem with critical power m = 2 − 2/d, we prove that all radial solutions with critical mass would converge to a family of stationary solutions, while all radial solutions with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
(60 reference statements)
0
18
0
Order By: Relevance
“…Calvez, Carrillo, and Hoffmann extended the latter result to general power-law interaction potentials −d < k < 0 [41,42]. Finally, in the Newtonian case, Yao showed that every radial solution with compact support will converge to some stationary solution in this family [146], though the asymptotic behavior of non-radial solutions remains unclear.…”
Section: Fair Competition Regime M = M Cmentioning
confidence: 90%
“…Calvez, Carrillo, and Hoffmann extended the latter result to general power-law interaction potentials −d < k < 0 [41,42]. Finally, in the Newtonian case, Yao showed that every radial solution with compact support will converge to some stationary solution in this family [146], though the asymptotic behavior of non-radial solutions remains unclear.…”
Section: Fair Competition Regime M = M Cmentioning
confidence: 90%
“…Both the aggregation-diffusion equation and constrained aggregation equation have gradient flow structures with respect to the 2-Wasserstein metric. The aggregation-diffusion equation is formally the gradient flow of the sum of an interaction energy and Rényi entropy Over the past fifteen years, there has been significant work on aggregation-diffusion equations, analyzing dynamics of solutions, asymptotic behavior, and minimizers of the energy E m [8,9,12,17,19,22,26,28,29,31,34,37,49,70,71]. The vast majority of the literature has considered one of two choices of interaction potential: either purely attractive power-laws or repulsive-attractive power-laws, K(x) = |x| p /p or K(x) = |x| q /q − |x| p /p for 2 − d p < q 2, q > 0, (1.3) with the convention that |x| 0 /0 = log(|x|).…”
Section: Introductionmentioning
confidence: 99%
“…Note that Theorem 6 does not imply such rigid behavior at blow-up for solutions with larger than critical mass. Mass comparison methods similar to those employed to prove finite time blow-up and the arguments in [5,45,38,30] are used to show that this concentration cannot occur in finite or infinite time. Hence, the solution must be global and uniformly bounded.…”
Section: Introductionmentioning
confidence: 99%